KATE EICHHORN, The Archival Turn in Feminism: Outrage in Order - Sheffield, Rebecka (Archivaria, 2014)
The Archival Turn in Feminism: Outrage in Order. KATE EICHHORN. Philadelphia: Temple University Press, 2013. xii, 188 pp. 978-1-4399-0951-5.